Measurement of the W+W- production cross section in pp̄ collisions at s=1.96TeV using dilepton events - Abazov, V. M. (2005)
We present a measurement of the W+W- production cross section using 184pb-1 of pp̄ collisions at a center-of-mass energy of 1.96 TeV collected with the Collider Detector at Fermilab. Using the dilepton decay channel W+W-→ℓ+νℓ-ν̄, where the charged leptons can be either electrons or muons, we find 17 candidate events compared to an expected background of 5.0-0.8+2.2 events. The resulting W+W- production cross-section measurement of σ(pp̄→W+W-)=14.6-5.1+5.8(stat)-3.0+1.8(syst) ±0.9(lum)pb agrees well with the standard model expectation. © 2005 The American Physical Society.